Evaluation of LipL32 and LigA/LigB Knockdown Mutants in Leptospira interrogans Serovar Copenhageni: Impacts to Proteome and Virulence - Fernandes, Luis G. V.; Putz, Ellie J.; Stasko, Judith; Lippolis, John D.; Nascimento, Ana L. T. O.; Nally, Jarlath E. (Frontiers in Microbiology, 2022)
Leptospirosis is a worldwide zoonosis caused by pathogenic species of the genus Leptospira. The recent application of CRISPR interference (CRISPRi) to Leptospira facilitates targeted gene silencing and provides a new tool to investigate pathogenic mechanisms of leptospirosis. CRISPRi relies on the expression of a catalytically “dead” Cas9 (dCas9), and a single-guide RNA (sgRNA). Previously our group generated a LipL32 and a double LigA/LigB (LigAB) mutant, which in the current study, were characterized by whole-cell proteomics in comparison to control leptospires harboring plasmid expressing dCas9 alone. Comparison of control and LigAB mutant leptospires identified 46 significantly differentially expressed (DE) proteins, including 27 proteins that were less abundant and 19 proteins that were more abundant in the LigAB mutant compared to the control. Comparison of control and LipL32 mutant leptospires identified 243 DE proteins, of which 84 proteins were more abundant and 159 were less abundant in the LipL32 mutant strain. Significantly increased amounts of known virulence impactors and surface membrane receptors including LipL45, LipL31, LigB and LipL41 were identified. The virulence of LipL32 and LigAB mutants were evaluated in the hamster model of leptospirosis; the LigAB mutant was unable to cause acute disease, although mutant leptospires could still be recovered from target organs, albeit at a significantly lower bacterial burden (<850 and <16-fold in liver and kidney, respectively, in comparison to control), indicating attenuation of virulence and a shift to chronic bacterial persistence. Notably, the LipL32 mutant displayed augmented virulence as evidenced by early onset of clinical symptoms and increased numbers of circulating foamy macrophages. Validation of LipL32 and LigAB mutants recovered from liver and kidney, in the presence or absence of antibiotic selection revealed high plasmid stability, and by extension, gene silencing, in vivo. Collectively, this work emphasizes the advantages and feasibility of using CRISPRi technology to evaluate and characterize virulence factors of leptospires, and their respective host-pathogen interactions, in animal models of leptospirosis. Importantly, it also provides insight into the requirements of LigA and LigB for acute disease, and explores the impact of silencing expression of lipL32 which resulted in substantial changes in amounts of outer membrane proteins.